A Unique C‐terminal Domain Allows Retention of Matrix Metalloproteinase‐27 in the Endoplasmic Reticulum. (6th February 2014) - Cominelli, Antoine; Halbout, Mathias; N'Kuli, Francisca; Lemoine, Pascale; Courtoy, Pierre J.; Marbaix, Etienne; Tyteca, Donatienne; Henriet, Patrick
<x xml:space="preserve">Abstract</x> We report that, unlike other matrix metalloproteinases (MMPs), MMP‐27 is retained in the endoplasmic reticulum due to its specific C‐terminal extension (CTE). Upon CTE removal, MMP‐27 accesses the intermediate compartment and Golgi and is constitutively secreted. Conversely, CTE addition to a secreted MMP (MMP‐10) causes ER retention and blocks secretion. We further show that MMP‐27 is not an integral membrane protein. Indeed, the CTE is not a transmembrane domain and MMP‐27 partitions in the aqueous phase after Triton X‐114 extraction.<boxed-text content-type="graphic" id="tra12149-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>